DOES CORPORATE GOVERNANCE INFLUENCE VALUE CREATION : ASSESSING THE MEDIATING ROLE OF CSR AND TAX AVOIDANCE - Itan, Iskandar; Antoni, Antoni (Jurnal Ekonomi Balance, 2021)
This study aims to investigate the influence of CG on value creation both directly and as a mediating role in the form of tax avoidance and CSR. The panel data approach was employed, using a sample of 32 multisectoral companies, excluding those in the financial sector, that are listed in the Indonesia Stock Exchange from 2016 to 2019. The data is analyzed using the Smart PLS. In this study, value creation was measured using Tobin’s Q  and CG was measured using the Corporate Governance Index (CGI); while the mediating variable, in the form of tax avoidance, was measured using the Henry & Sansing formula, and CSR was measured using the GRI-G4 index. The result showed that corporate governance has a direct significant impact on value creation. Furthermore, it is found that CSR & tax avoidance could not mediate the relationship between CG and value creation.